1965
DOI: 10.1084/jem.122.4.745
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the Mouse Intestine With Escherichia Coli

Abstract: Although enteropathogenic strains of Esckerickia coli are a frequent cause of disease in human infants, it has proven difficult to establish experimental infections in animals with these organisms. The most successful results so far have been obtained by feeding cultures to mice treated with antibacterial drugs prior to the test in order to suppress their indigenous intestinal flora (1). Useful as it is, this method is obviously artificial and fails to reproduce the conditions under which the disease is common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…These have been reviewed elsewhere (1012) and include the contribution to digestion (such as the ability of microbes to break down host nondigestible polysaccharides) and its secondary benefits (the generation of SCFA), the metabolism of xenobiotics, which aids in protection from environmental toxins, and, as briefly discussed here, colonization resistance. The origin of the concept of colonization resistance dates to the studies of Dubos in 1965 who demonstrated the role of the indigenous microbiota in antagonizing colonization with a potential pathogen (13). It is now appreciated that this protective function is probably woven into the many symbiotic functions of the commensal microbiota (14).…”
Section: “Colonization Resistance” and The Risk Of Enteropathogenic Imentioning
confidence: 99%
“…These have been reviewed elsewhere (1012) and include the contribution to digestion (such as the ability of microbes to break down host nondigestible polysaccharides) and its secondary benefits (the generation of SCFA), the metabolism of xenobiotics, which aids in protection from environmental toxins, and, as briefly discussed here, colonization resistance. The origin of the concept of colonization resistance dates to the studies of Dubos in 1965 who demonstrated the role of the indigenous microbiota in antagonizing colonization with a potential pathogen (13). It is now appreciated that this protective function is probably woven into the many symbiotic functions of the commensal microbiota (14).…”
Section: “Colonization Resistance” and The Risk Of Enteropathogenic Imentioning
confidence: 99%
“…Historically, laboratory mice have been used as experimental E. coli infection models [14]. E. coli colonizing the intestine are often considered commensals in laboratory mice and rats, but have been implicated in cases of bacterial infections in laboratory mice [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the coevolved symbiotic relationship between microbes and humans, the indigenous microbiota provides many crucial functions to the host. In fact, the origin of the concept of colonization resistance dates back to 1965, when the role of the microbiota in antagonizing colonization with a potential pathogen was demonstrated (160). The introduction of broad-spectrum antimicrobial agents, in particular, provided the first evidence of the impact of loss of constituents of the microbiota (161).…”
Section: The Host and The Host Microbiotamentioning
confidence: 99%